2013
DOI: 10.1248/bpb.b12-00885
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Tissue-Specific Action of the Selective Androgen Receptor Modulator S-101479

Abstract: Selective androgen receptor modulators (SARMs) comprise a new class of molecules that induce anabolic effects with fewer side effects than those of other anabolic agents. We previously reported that the novel SARM S-101479 had a tissue-selective bone anabolic effect with diminished side effects in female animals. However, the mechanism of its tissue selectivity is not well known. In this report, we show that S-101479 increased alkaline phosphatase activity and androgen receptor (AR) transcriptional activity in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 56 publications
2
20
0
2
Order By: Relevance
“…15 • SARMs with tetrahydroquinolinone core structure, such as S-40503, 15 S-101479, 21 and S-49288. 22 • SARMs with indole core structure, such as RAD35010 15 and Ly2452473. 21 • SARMs with steroidal core structure, such as MK-0773, 15,23 Cl-4-AS-1, TMF-4AS-1, YK-11, and S-42.…”
mentioning
confidence: 99%
“…15 • SARMs with tetrahydroquinolinone core structure, such as S-40503, 15 S-101479, 21 and S-49288. 22 • SARMs with indole core structure, such as RAD35010 15 and Ly2452473. 21 • SARMs with steroidal core structure, such as MK-0773, 15,23 Cl-4-AS-1, TMF-4AS-1, YK-11, and S-42.…”
mentioning
confidence: 99%
“…7,14,32,35,37 SERMs and SARMS have convincingly demonstrated that small molecules can elicit tissue-or gene-selective effects, and recently, several groups have developed inhibitors that disrupt interactions between NRs and coactivator proteins. 7,14,31,32,35,37,38 For example, the bone-specific actions of the SARM S-101479 are the result of its failure to recruit TIF2, SRC-1, and NCoA3. 38 We have previously described an AR-TIF2 PPI biosensor (PPIB) HCS assay that can be used to screen for compounds that can induce, inhibit the formation of, or disrupt preexisting PPIs between AR and TIF2.…”
Section: Introductionmentioning
confidence: 99%
“…7,14,31,32,35,37,38 For example, the bone-specific actions of the SARM S-101479 are the result of its failure to recruit TIF2, SRC-1, and NCoA3. 38 We have previously described an AR-TIF2 PPI biosensor (PPIB) HCS assay that can be used to screen for compounds that can induce, inhibit the formation of, or disrupt preexisting PPIs between AR and TIF2. 20 However, the previous AR-TIF2 PPIB studies were conducted in the U-2 OS osteosarcoma cell line, and we wanted to determine whether the assay might perform differently when performed in a CaP cell background and whether AR-TIF2 PPI inhibitor or disruptor hits would behave differently.…”
Section: Introductionmentioning
confidence: 99%
“…A recent report has demonstrated that the SARM, S-101479, which shows low N/C interaction, induced recruitment of fewer cofactors than DHT. 34) This observation suggests that the difference in Fst mRNA regulation between YK11 and DHT stems from cofactor recruitment differences.…”
Section: Discussionmentioning
confidence: 98%